Synthesis and Anticancer Evaluation of Novel 10-Methoxycamptothecin Derivatives - Zhu, Meixuan; Jing, Lijia; Wang, Shaoming; Zhang, Sheng; Wang, Yang (Asian Journal of Chemistry, 2015)
As part of our continuing search for potential anticancer drug candidates, we have synthesized four 10-methoxycamptothecin derivatives. The compounds were synthesized by facile procedures and characterized by 1H NMR, 13C NMR and mass spectra study. The synthesized compounds were examined for their cytotoxic effect on a panel of five human cancer cell lines. Three out of five compounds were found to exhibit moderate anticarcinogenic activities in all cell lines. The result of the present investigation encourage us to develop more other related compounds and to screen them for a wide range of biological activity.